Experimental study of aerodynamic coefficients of a combined blade - Н.К. Танашева; А.Р. Бахтыбекова; Н.Н. Шуюшбаева; А.Н. Дюсембаева; М.А. Бурков; С.А. Нуркенов (Қарағанды университетінің хабаршысы. Физика сериясы)
Magnus wind turbines have a number of advantages in the form of electricity generation at low wind values, ranging from 3-4 m/s. However, at high speeds around the existing blades of wind turbines, there is a phenomenon of separation of vortices, which entails the destruction of the structure, as well as an increase in drag. Based on this, an urgent issue is the regulation of the flow around cylindrical bodies, along with a decrease in drag force. The novelty of the work is the elimination of vortices, as well as their control, by adding a fixed blade to the cylinder. Authors of the article for this purpose created a mock-up of the cylinder blade with a fixed blade. A number of experimental studies were carried out to determine the aerodynamic forces and coefficients depending on the angle of inclination with respect to the incoming flow at U = 5 m/s. It was found that at an angle of inclination of 0° and 180°, the combined blade has a maximum lifting force of 2.7 N and 2.75 N, respectively. It is determined that at these angles, the drag force is the lowest and is 1.26 N and 1.08 N.